Oral health-related conditions in Ecuador: A temporal trend analysis of hospital discharges from 2000-2023. - Verónica Baldeón; Adriana Hernández; Sthephany Tapia; Alejandro Rodriguez (PLoS ONE)
Background Monitoring hospitalization rates associated with oral health conditions is an important part of epidemiological surveillance, especially when these conditions have increased significantly in low-and middle-income countries. This study aimed to evaluate the temporal trends in hospital discharges associated with oral health-related conditions in Ecuador from 2000 to 2023 and identify the leading diagnoses groups. Methods An ecological time-series study was conducted based on annual data from the National Institute of Statistics and Censuses of Ecuador. We identified oral conditions using hospital discharge records, which were classified according to the International Classification of Diseases. We estimated crude and age-standardized rates per 100,000 inhabitants for the entire population and crude rates by sex, age, region, and the diagnosis. Joinpoint analysis was used to identify national trends in hospital discharges. Results A total of 93652 hospitalizations were identified. Malignant tumors of the head, face, and neck were the most common diagnosis attributed to hospital discharges (16.5%), followed by cleft palate (14.5%) and cleft lip (7.8%) and other diseases of the jaws (5.4%). The crude rate of OHRC increased from 17.94 to 28.81 hospitalizations per 100,000 population between 2000 and 2023. Based on joinpoint analysis, hospital discharges increased by 2.2% annually during the study period. However, three temporal trends were identified: from 2000 to 2017, hospital discharges increased annually by 4.3% (p<0.05); from 2017 to 2020 decreased by 17.2%; and from 2020 to 2023 increased annually by 12.9%. Average hospitalization rates were higher among those aged 0-9 and > 64 years. Conclusions Hospitalization rates associated with oral health-related conditions in Ecuador have increased significantly over the past twenty-four years, except during the COVID-19 pandemic, where cases dropped considerably. Many of the oral conditions identified in the study were malignancies, which are caused by a complex relationship between genetic, environmental, and behavioral factors. Conducting early detection analysis is essential to reduce their occurrence.